Introducing the Adsorption Energy Distribution Calculation for Two-Component Competitive Adsorption Isotherm Data - Haseeb, Abdul; Wondmagegne, Yosief; Fernandes, Miguel X.; Samuelsson, Jörgen (Analytical chemistry (Washington), 2025)
This work introduces the Adsorption Energy Distribution (AED) calculation using competitive adsorption isotherm data, enabling investigation of the simultaneous AED of two components for the first time. The AED provides crucial insights by visualizing competitive adsorption processes, offering an alternative adsorption isotherm model without prior assuming adsorption heterogeneity, and assisting in model selection for more accurate retention mechanistic modeling. The competitive AED enhances our understanding of multicomponent interactions on stationary phases, which is crucial for understanding how analytes compete on the stationary phase surface and for selecting adsorption models for numerical optimization of preparative chromatography. Here, the two-component AED was tested on both synthetic and experimental data, and a very successful outcome was achieved.